calc help

consider the function f(x)= x^2/4 -6
Rn is the Riemann sum where the sample points are chosen to be the right-hand endpoints of each sub-interval.


Calculate Rn for f(x)= x^2/4 -6 on the interval [0,4] and write your answer as a function of n without any summation signs.
Rn= ?
please help

The k-th term in the summation is:

[(s*k)^2/4 - 6]*s

s is the step between two terms and is 4/n. k ranges from 1 to n. n is the number of parts in which you have divided the interval [0,4]. So, if you take n = 1 then s = 4 and you are then only evaluating the function x = 4, which is the right hand endpoint of the interval.

If you n = 2 then s = 2 and n ranges from 1 to 2. The function is ten evaluated at 1*s and 2*s, i.e. at 2 and 4 and the values are multiplied by 2.

To evaluate the summation we write:

[(k*4/n)^2/4 - 6]*4/n

= k^2 16/n^3 - 24/n

The last term is - 24/n. If we sum this from k = 1 to n then that amounts to mulitplying by n, so that yields -24.

To evaluate te first term we must calculate:

Sum from k=1 to n of k^2.

You can look up the formula for that (it's a third degree polynomial in n), but it is more fun to derive this yourself.

You can use the formula for the geometric series:

Sum from k=0 to n of a^k =

[1-a^(n+1)]/[1-a]

Differentiate both sides w.r.t. a:

Sum from k=1 to n of ka^(k-1) =

- (n+1)a^(n)/(1-a) + [1-a^(n+1)]/[1-a]^2

If you take the limit a-->1 on both sides you get the formula for the sum of k from 1 to n. We want the sum of k^2. If you differentiate again w.r.t. a a factor (k-1) comes down. That's not what we want, we want a factor k. So, you first multiply both sides by a and then you differentiate w.r.t. a. Then you take the limit a -->1 on both sides.

A faster way to calculate the summation is as follows.

Sum from k=0 to n of a^k =

[1-a^(n+1)]/[1-a]

Substitute a = exp[x] in here:

Sum from k=0 to n of exp[kx] =

[exp[(n+1)x] - 1]/[exp(x) - 1]

Expand both sides in powers of x. You can see that the coefficient of x^2 yields 1/2 times the desired summation.

To find the series expansion of the function

[exp[(n+1)x] - 1]/[exp(x) - 1]

you equate it to an unknown series:

c_0 + c_1x + c_2 x^2 + ...

This yields:

[c_0 + c_1x + c_2 x^2 + ...]*

[x + x^2/2 + x^3/6 + ...] =

(n+1)x + (n+1)^2x^2/2 + (n+1)x^3/6 + ...

And you find that:

c_0 = n+1

c_1 = 1/2 n(n+1)

c_2 = 1/6 n(n+1/2)(n+1)

The summation is 2c_2, so:

Sum from k = 1 to n of k^2 =

1/3 n(n+1/2)(n+1)

This means that the Riemann sum of the first term is:

16/3 n(n+1/2)(n+1)/n^3

  1. 👍 0
  2. 👎 0
  3. 👁 235
asked by amanda

Respond to this Question

First Name

Your Response

Similar Questions

  1. Calculus

    Evaluate the Riemann sum for (x) = x3 − 6x, for 0 ≤ x ≤ 3 with six subintervals, taking the sample points, xi, to be the right endpoint of each interval. Give three decimal places in your answer and explain, using a graph of

    asked by nan on March 10, 2016
  2. calculus

    consider the function f(x)= x^2/4 -6 Rn is the Riemann sum where the sample points are chosen to be the right-hand endpoints of each sub-interval. Calculate Rn for f(x)= x^2/4 -6 on the interval [0,4] and write your answer as a

    asked by amanda on November 30, 2006
  3. Calc 2

    Can you give me the step by step instructions on how to do this problem? I'm having difficulty understanding Riemann Sum. Let f(x) = 2/x a. Compute the Riemann sum for R4 using 4 subintervals and right endpoints for the function

    asked by Bae on May 2, 2014
  4. Calculus

    Evaluate the Riemann sum for (x) = x3 − 6x, for 0 ≤ x ≤ 3 with six subintervals, taking the sample points, xi, to be the right endpoint of each interval and please explain, using a graph of f(x), what the Riemann sum

    asked by Adrianna on March 11, 2016
  5. Calculus

    (a) Find the Riemann sum for f(x) = 7 sin x, 0 ≤ x ≤ 3π/2, with six terms, taking the sample points to be right endpoints. (Round your answers to six decimal places.) I got 3.887250 as an answer, but that's not right. (b)

    asked by John on November 16, 2011
  6. Calculus, Riemann

    IF ANYONE CAN PLEAAAASEEEE HELP ME Use the Riemann sum definition of the definite integral to show that b 3 ¡ò x©÷dx - b©ø -a©ø a Here, for simplicity, we assume b > a > 0. Be sure to clearly specify your mesh/grid xi, ,

    asked by Ellen D on May 7, 2014
  7. calculus

    Consider the given function. f(x) = 3 sin(6x) text(, ) 0

    asked by Justin on January 18, 2008
  8. calculus

    Consider the given function. f(x) = 3 sin(6x) text(, ) 0

    asked by Justin on January 18, 2008
  9. calc

    If f(x) = 3x^2 − 2x, 0 ≤ x ≤ 3, evaluate the Riemann sum with n = 6, taking the sample points to be right endpoints.

    asked by sara on April 16, 2015
  10. Calculus

    The Riemann sum s for f(x)=4x^2, 0

    asked by Alice on April 19, 2016

More Similar Questions